Diminutive colorectal polyp resection comparing hot and cold snare and cold biopsy forceps polypectomy. Results of a pilot randomized, single-center study (with videos) - Gómez, Victoria; Badillo, Raul J.; Crook, Julia E.; Krishna, Murli; Diehl, Nancy N.; Wallace, Michael B. (Endoscopy International Open, 2015)
Background: The optimal method of diminutive polypectomy (< 6 mm) is unknown.Objective: To assess the rates of incomplete resection of diminutive polyps of the colon using three standard polyp resection techniques (hot snare, cold snare, and cold biopsy forceps).Design: Randomized, pilot study.Settings: Single-center endoscopy center.Patients: Patients undergoing routine outpatient colonoscopies.Interventions: Polypectomy was performed using the method to which the patient was randomized. Following retrieval of the polyp, the polypectomy base was lifted by submucosal injection of normal saline and then excised using the cold snare device. If no tissue could be removed, then at least four cold biopsies using forceps of the remaining margin were obtained.Main outcome measures: Adequacy of resection of diminutive polyps, which was defined as no visible adenoma or hyperplastic tissue seen in the base tissue on histology.Results: A total of 60 patients were enrolled (57 % male), the mean age was 60 (range 33 – 82), and 62 polyps were randomized from 37 patients. The mean polyp size was 3.6 mm (range 2 – 5 mm) and 37 polyps (60 %) were adenomatous. Overall incomplete polyp resection rate was 9 % (95 %CI 3 – 19 %), 5 of 37 (14 %) for adenomas. By the study arm, the incomplete resection rates were 1 of 18 (6 %) for hot snare, 2 of 21 (10 %) for cold snare, and 2 of 18 (11 %) for cold biopsy forceps. The majority of polyp bases were removed with cold biopsy forceps since most of the endoscopists did not feel that the saline lift cold snare method was feasible or appropriate.Limitations: Small sample size; endoscopic mucosal resection (EMR) of the polyp base tissue was not routinely performed.Conclusions: Recruiting patients to a pilot study that randomized polyps to one of three common methods of polypectomy for diminutive polyps was feasible, and approximately 1 in 10 diminutive polyps found on colonoscopy were incompletely resected by standard polypectomy methods.